80 will be the new 70: Old‐age mortality postponement in the United States and its likely effect on the finances of the OASI program. Issue 2 (16th July 2020) - McCarthy, David
Abstract: Using a Bayesian cohort‐based mortality model, we identify strong evidence of mortality postponement at older ages in the United States. We use the results of the model to project mortality rates 75 years ahead, and show that this will likely raise the U. S. old‐age dependency ratio to 55% by 2090 ( 30% larger than the Social Security Administration [SSA] intermediate estimates). We estimate how this will affect the finances of the Old‐Age and Survivors Insurance program as modeled by the SSA. In our median estimate, using the SSA's intermediate‐cost assumptions, mortality postponement will raise the open‐system unfunded liability over a 75‐year period by around 6.8trn over SSA estimates, worsening the actuarial balance of the program by an extra 1.30% of taxable payroll. Mortality postponement will also have significant implications for other government programs, notably Medicare, and for private‐sector financial intermediaries, such as pension funds and insurance companies, as well as private households.